2017
DOI: 10.1016/j.redox.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NLRP3 inflammasome activation and arterial neointima formation associated with acid sphingomyelinase during hypercholesterolemia

Abstract: The NLRP3 inflammasome has been reported to be activated by atherogenic factors, whereby endothelial injury and consequent atherosclerotic lesions are triggered in the arterial wall. However, the mechanisms activating and regulating NLRP3 inflammasomes remain poorly understood. The present study tested whether acid sphingomyelinase (ASM) and ceramide associated membrane raft (MR) signaling platforms contribute to the activation of NLRP3 inflammasomes and atherosclerotic lesions during hypercholesterolemia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 71 publications
3
77
0
1
Order By: Relevance
“…The mouse carotid arterial endothelial cells were isolated and characterized as described earlier [20, 21]. For the TMAO stimulation, cells were treated with TMAO (30 μm) and then incubated for overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The mouse carotid arterial endothelial cells were isolated and characterized as described earlier [20, 21]. For the TMAO stimulation, cells were treated with TMAO (30 μm) and then incubated for overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Recent study demonstrated that ASM and ceramide contribute to NLRP3 inflammasome formation and activation in hypercholesterolemia mice (Koka et al, 2017). 7-ketocholesterol or cholesterol crystals dramatically induced the formation and activation of NLRP3 inflammasomes, clustering of NLRP3-ASCcaspase-1 complex, activation of caspase-1, and production of IL-1β, these events were dramatically suppressed by gene silence of ASM, pharmacological inhibition, or gene deficiency in mice carotid arterial endothelial cells (CAECs).…”
Section: Asm Links Damps With the Inflammasomementioning
confidence: 99%
“…Emerging studies have revealed that acid sphingomyelinase (ASM) plays crucial role in the activation of inflammasomes (Grassmé et al, 2014;Boini et al, 2016;Koka et al, 2017). ASM is an enzyme that functions to catalyze sphingomyelin into ceramide (Gatt, 1963).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several SL metabolites have been associated with the development of several pathologies, including diabetes, cancer, microbial infections, neurological syndromes and cardiovascular disease . Our laboratory previously reported that acid sphingomyelinase (ASM) plays an important role in glomerular injury and inflammasome activation …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Our laboratory previously reported that acid sphingomyelinase (ASM) plays an important role in glomerular injury 17,18 and inflammasome activation. 19,20 Acid sphingomyelinase (ASM), a lysosomal enzyme, is present in lysosomes and secretory lysosomes, and its fusion with plasma membrane results in the release of ceramide on the outer leaflet of the plasma membrane that serves to re-organize and cluster receptors and signalling molecules. 21,22 This re-organization of receptors and associated signalling molecules mediates various effects of ceramides at the cellular level.…”
Section: Introductionmentioning
confidence: 99%